Strategi Pembinaan Program Unggulan Tahfidz Al-Quran Di Man 1 Kota Malang (Mahad Darul Hikmah) - Zakkiyah, Firda; Samsul Ulum, Mohammad; Nurul Kawakip, Akhmad (Universitas Pakuan, 2025)
STRATEGY FOR DEVELOPING THE OUTSTANDING QURAN MEMORIZATION PROGRAM AT MAN 1 KOTA MALANG (MAHAD DARUL HIKMAH)Memorizing the Quran is a gift that requires great effort and a strong and continuous commitment to maintaining its verses. In memorizing the Quran and facing its challenges, an appropriate coaching strategy is certainly needed to achieve the set goals. This study aims to describe how the coaching strategy of the flagship Quran memorization program is carried out at Mahad Darul Hikmah, Madrasah Aliyah Negeri 1 Malang City. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The results of this study indicate that coaching is carried out in groups and each group is led by its respective ustadz/ustadzah. The coaching strategy is carried out by dividing the target of at least 2 juz in regular classes and 6 juz in religious classes. The supervising teacher uses a continuous system to maintain student memorization, the teacher will also conduct tasmi to evaluate student memorization and will also conduct an oral exam in grade 12 based on the predetermined targets. This flagship tahfidz program has had a positive impact on students' memorization achievements, enabling them to optimize their memorization, win tahfidz championships in competitions, and complete their memorization.